Pemikiran Ibnu Khaldun Tentang Mekanisme Pasar - Wulpiah, Wulpiah (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
Ibnu Khaldun is a thought-leader who is proficient in the various fields of study such as politics, social, philosophy, history, and economy. So, Ibnu Khaldun is known as one of the originators of economic theory and as the largest Muslim economists recognized by Western economists. Unlike previous scholars who had tendencies to be normative, Ibnu Khaldun used historical and social approach to understand economy of a nation. Ibnu Khaldun was very positive in comprehending economy. So, his ways of thinking will be very worthy to put forward in this paper, especially on market mechanisms. Market is a place where buyers and sellers meet and do transactions of buying and selling goods or services. The importance of market in Islam cannot be separated from the function of the market as a place for buying and selling activities. Sale and purchase itself has an important function, since buying and selling are parts of the economic activities which are "accredited" in Islam. Islam is very concerned with buying and selling as one of the economic fundamentals. It can be seen in Al-Baqarah 275 saying that "God justifies the purchase and forbids usury". The market mechanism is a system that determines the formation of prices, which is in the process can be influenced by many things: demand and supply, distribution, government policies, labor, money, taxes and security. In the process of market mechanisms requires the principles of morality, such as fair competition (fair play), honesty, transparency and justice.